Natural Frequencies of Waves In Helical Springs - Qurbonovich, Esanov Nuriddin (Research Parks Publishing LLC, 2025)
This paper explores the natural frequencies of vibrations in helical springs through both theoretical analysis and computational methods. Helical springs are crucial elastic components widely used in various mechanical systems, serving primarily to absorb loads and mitigate vibrations. The accurate determination of their natural frequencies is vital for optimizing the performance and ensuring the safety of machines. The study introduces a mathematical model and computational scheme for calculating the natural frequencies of helical springs, providing a comprehensive analysis of the results obtained. By combining theoretical foundations with computational techniques, this paper contributes to the understanding of spring dynamics and offers practical insights for the design of mechanical systems.